Exploring the relationship between sleep patterns and depression among Chinese middle school students: a focus on sleep quality vs. sleep duration - Zhang, Xinkai; Dou, Zhaobo; Yang, Fengying; Luo, Lin; Yang, Jie (Frontiers in Public Health, 2024)
Objective: This study aims to explore the relationship between sleep patterns and depressive symptoms among adolescents, examining variations in depressive symptoms across different sleep qualities, durations, and habits.A cross-sectional survey was conducted, gathering data from 8,775 Chinese adolescents on their demographics, lifestyle habits, sleep quality and duration, and depressive symptoms. The association between sleep parameters and depressive symptoms was analyzed using multivariate logistic regression.The findings reveal a significant correlation between sleep quality/duration and depressive symptoms. Specifically, adolescents with poor sleep quality had higher depressive scores (mean score = 14.62, standard deviation = 5.71), significantly exceeding those with better sleep quality (mean score = 11.54, standard deviation = 4.69). Adolescents with shorter sleep duration also showed significantly higher depressive scores than those with moderate sleep duration. Importantly, adolescents experiencing both poor sleep quality and shorter sleep duration were at a significantly increased risk of depressive symptoms (OR = 4.04, 95% CI: 3.53-4.62, P < 0.001).Further analysis indicated that older age and lower family economic status were independent predictors of a higher risk of adolescent depression (OR = 1.22, 95% CI:1.08-1.38, P = 0.001), whereas factors such as gender, ethnicity, residence, being an Sleep Habits 删除[萝]: sleep habits 删除[萝]: significantly associated with 删除[萝]:only child, and parental education levels were not statistically significant.Conclusion: Among Chinese adolescents, poor sleep quality and shorter sleep duration are independent predictors of higher depressive symptom scores. Adolescents experiencing both of these conditions simultaneously have a significantly increased risk of depressive symptoms. Furthermore, older age and lower family economic status are also significantly related to an increased risk of depression in adolescents.These findings emphasize the importance of improving sleep quality and optimizing sleep duration for the prevention of adolescent depression. They also suggest the need for a comprehensive approach that addresses the multifaceted factors influencing adolescent mental health, including sleep patterns and socioeconomic disparities.